Promoting Aboriginal employment in the mining industry: a case study from the Goldfields Region of Western Australia - Bonney, Dennis Noel (Curtin University, 2005)
Over the past two decades, various efforts have been made to increase Aboriginal access to the employment and business opportunities offered by Australia’s mining industry. Those efforts have been given greater impetus by the High Court’s landmark Mabo judgment of 1992 and by the subsequent native title legislation (1993) and the judicial and negotiation processes and outcomes to which it has given rise, including negotiated agreements regarding mining industry access to and use of Indigenous lands. Such initiatives have placed Aboriginal people in a more equitable negotiating position with respect to mining industry developments. Nevertheless, in an overall sense, Aboriginal people remain essentially marginal to the mining industry, with their employment, career and business opportunities still very much underdeveloped.My research examines a training initiative (the Aboriginal Training Program) designed to encourage greater Aboriginal participation in the mining industry in the Eastern Goldfields region of Western Australia. The central question addressed in my research is how effective the Aboriginal Training Program (ATP) has been in advancing Aboriginal employment and career opportunities in the mining industry. This broad research question has given rise to a number of more specific research objectives:• To identify and examine the background and characteristics of the ATP’s enrolees and graduates. • To document the experiences of the ATP participants, both within the program itself and subsequent to it. • To examine the impact of the program in encouraging greater Aboriginal participation in the mining industry. • To identify factors currently limiting the employment and career advancement in the mining industry of ATP graduates. • To identify ways in which the program might be modified to enhance its effectiveness in promoting greater Aboriginal participation in the mining industry.In conducting my research, I have tried to present an Indigenous rather than non-Indigenous perspective on the program. To this end, I conducted in-depth, semi-structured interviews with 15 recent ATP graduates, the matters examined ranging across the factors that initially aroused their interest in the ATP, the enrolment process, their experiences within the program, and their experiences subsequent to their graduation.Emerging from my research is a picture of mixed success and mixed perspectives. Generally, all of the interviewees were supportive of the idea and ideals of the ATP, believing it to be an important and overdue initiative. There was also strong though not unanimous support for the ATP as it has worked in practice. Various viewpoints were in evidence in this connection, but there was a broadly-based feeling that the program could be made to work to better effect. There were also specific suggestions about how the ATP’s effectiveness could be enhanced, both by changes within the program itself and by better back-up and support by mining industry employers and supervisors.